Building corporate reputation through social media marketing efforts: the mediating role of corporate brand credibility. (26th October 2022) - Garanti, Zanete; Igbudu, Nicholas; Popoola, Temitope; Vrontis, Demetris; Melanthiou, Yioula
Social media is a widely used tool by companies to communicate with their customers. This study explores customers' perception of social media marketing efforts by companies and their role in enhancing corporate reputation. It also evaluates the mediating role of corporate brand credibility in the relationship between social media marketing efforts and corporate reputation. Data for this study was adopted from 404 customers of the retail banking sector in Latvia, contacted via social media platforms such as Facebook using the non-random snowball sampling method. The structural equation modelling technique was used to test the relationship of the study variables. The study results show a direct and significant influence of social media marketing efforts on corporate brand credibility. However, social media marketing efforts do not have a significant impact on corporate reputation. Corporate brand credibility has a positive direct impact on corporate reputation. Therefore, it is shown that corporate brand credibility mediates the relationship between social media marketing efforts and corporate reputation.